Designing English Module for Guides of Museum Pustaka Lontar, Karangasem, Bali - Koeswiryono, Dika Pranadwipa; Suadnyana, I Wayan; Supartini, Ni Luh (Jurnal Kajian Bali (Journal of Bali Studies); Vol 13 No 1 (2023): Volume 13 No 1 April 2023, 2023)
Museum Pustaka Lontar in Karangasem, Bali, has preserved and promoted lontars , the manuscripts that carried the ancient texts of Balinese tradition. This research and development study constructed an English module for the local guides at the lontar museum. The needs analysis derived from the observation of the museum, and interviews with the guides, investigated the guides’ necessities, lacks, and wants in learning English. The result showed that the local guides needed modules where the materials correspond to the guiding sequences of the museum. The materials had to also accommodate the translation of museum lontar-specific terms into English. Conversation-based materials were the most requested, as it resembled their daily interaction with visitors. These findings served as the base for the material development of the English module. Guides, language learners, and teachers in the tourism field might source their learning from the module.